Analysis of Factors Influencing Decision Making of Automotive Services at Cimobil Workshop, Jatiranggon Bekasi - Wulan Sari, Wulan Sari; Tina Rosa, Tina Rosa; Bachtar Bakrie, Bachtar Bakrie (Journal of Entrepreneur and Business, 2023)
This study aims to determine: a. Is there an effect of the product on purchasing decisions at the CIMobil Jatiranggon Bekasi workshop?b. Is there an effect of location on customer purchasing decisions at CIMobil Jatiranggon Bekasi workshops? c. Is there an effect of price on customer purchasing decisions at CIMobil Jatiranggon Bekasi workshops? d. Is there an effect of Promotion on Customer Purchase Decisions at CIMobil Jatiranggon Bekasi workshops?. This research is a survey research. The population in this study were workshop customers who lived in the area around the location, namely Metro (Bekasi) and DKI Jakarta, totaling 250 people. The sampling technique used purposive sampling method with Slovin calculations of 154 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The research analysis used SEM-PLS. The test results showed that the results of the validity and reliability tests of the instrument were stated to be valid and reliable. Loading factor shows a value above 0.5. which concluded that the instrument was valid and met convergent validity. Another illustration is shown in the Average Variance Extracted (AVE) test value above 0.5 for all constructs contained in the research model. the reliability test of Cronbach's Alpha value for all constructs was above 0.6. The results of the hypothesis test showed that the two variables studied, namely product and price variables, did not have a significant effect so the hypothesis was rejected. Meanwhile, two other variables, namely location and promotion variables, proved to have a significant relationship and the hypothesis was accepted. The R Square test results yielded a value of 0.749 meaning that all the variables studied had an influence of 74.9% on Purchase Decisions and the rest were influenced by other factors Meanwhile, two other variables, namely location and promotion variables, proved to have a significant relationship and the hypothesis was accepted. The R Square test results yielded a value of 0.749 meaning that all the variables studied had an influence of 74.9% on Purchase Decisions and the rest were influenced by other factors Meanwhile, two other variables, namely location and promotion variables, proved to have a significant relationship and the hypothesis was accepted. The R Square test results yielded a value of 0.749 meaning that all the variables studied had an influence of 74.9% on Purchase Decisions and the rest were influenced by other factors Keywords: Product, Location, Price, Promotion, Decision Making